The genus Carpesium: A review of its ethnopharmacology, phytochemistry and pharmacology. (2nd April 2015) - Zhang, Jian-Ping; Wang, Guo-Wei; Tian, Xin-Hui; Yang, Yong-Xun; Liu, Qing-Xin; Chen, Li-Ping; Li, Hui-Liang; Zhang, Wei-Dong
Abstract: Ethnopharmacological relevance: The plants in the genus Carpesium, which grow naturally in Asia and Europe, have long been used in traditional Chinese, Korean and Japanese medicines. The antipyretic, antimalarial, haemostatic, anti-inflammatory and detoxifying properties of their extracts enabled their use in the treatment of several diseases, such as fevers, colds, contusions, diarrhoea, mastitis, mumps, hepatitis, malaria, etc. This review summarises the state-of-the-art and comprehensive information surrounding its use as traditional medicine, phytochemistry, pharmacology, and toxicology to reveal the potential therapeutic effects of Carpesium plants and to establish a solid foundation for directing future research. Materials and methods: The extensive reading and investigation were actualised by systematically searching the scientific literatures including Chinese, Korean and Japanese herbal classics, library catalogs and scientific databases (PubMed, Scopus, SciFinder and the Web of Science), were systematically searched for topics related to factors like the chemical constituents, pharmacognostic research and pharmacological effects of the Carpesium species. Results: Carpesium plants have been studied extensively as traditional folk medicines in China, Korea and Japan all the time. In past, phytochemical research was the focal point of this genus, and the recent studies of the members of this genus have been focused on the pharmacological activity and potential therapeutic applications of these plants. The research performed revealed that 143 compounds including sesquiterpenoid lactone monomers, sesquiterpenoid lactone dimers, monoterpenes, diterpenoids, phenolic compounds, and several other type of compounds, were isolated and identified within this genus in recent years, and certain of these constituents had demonstrated to possess anti-inflammatory, anti-tumor, anti-plasmodial, anti-oxidant, anti-fungal and anti-bacterial effects. Conclusions: This review shows that approximately 50 active compounds possess therapeutic potential during the treatment of cancer, inflammatory, parasitosis, etc. However, apart from those bioactive molecules, a considerable part of compounds, including a lot of sesquiterpenes, and several other type of compounds that have been previously isolated but have not been tested biologically need to be further tested. Therefore, more pharmacological experiments should be focused on these untested chemical constituents. Additionally, another issue concerns that most pharmacological studies were only performed in vitro-based experiments, so additional in vivo tests in animal models are required to estimate their side effects for the safety approval of therapeutic applications. Finally, further studies through well controlled, double-blind clinical trials are required to re-evaluate their efficacious and possible side effects, and more pharmacological mechanisms on main active compounds will also be needed for illuminating correlations between ehnopharmacology and pharmacology in future. Graphical abstract: